Effect of the Quiet Eye Training on Motor Learning of Pistol Shooters - Jaleh Bahramian-Dehkordi; Saleh Rafiee; Jaleh Bagherli; Sayed Mohammadkazem Vaezmousavi (Vesnu Publications, 2020)
Introduction: A quiet eye is a key predictor in the efficient implementation of the inhibitory tasks and targeting. This study aims to investigate the effect of quiet eye training on improving the performance of pistol shooters.Materials and Methods: This was a controlled clinical trial study in which the participants included 20 male and female shooters with an average age of 22 years and a record between 545 and 555 m. The subjects were purposively selected from among 60 male and female shooters who participated in the 10-meter pistol race and in the country's top competitions. Ater completing the consent form, the subjects were classified from the highest score to the lowest score based on the pre-test scores and were placed in two groups as one in between (ABBA method) (10 in quiet eye training and 10 in technical training). The participants performed 10 attempts at each of the pre-test, post-test, and retention tests. The training protocol of the quiet eye group was in accordance with the pattern obtained from the elite shooter pattern along with the verbal instruction for 8 sessions and in 6 blocks of 10 consecutive shoots. Data was analyzed through the independent t-test, repeated measures analysis of variance (ANOVA), and Bonferroni post-hoc test in the SPSS software (version 20, IBM Corporation, Armonk, NY, USA) at the level P < 0.050. Results: The repeated measures ANOVA results of the study groups (from pre-test to retention) showed that these changes were significant for the quiet eye training group (P ≤ 0.001). According to the results of the Bonferroni post-hoc test, the quiet eye training group had a better shooting function in the post-test (P ≤ 0.010) and retention (P ≤ 0.020) stages compared to the pre-test. The results of the independent t-test indicated that there was a significant difference between the quiet training and technical groups in the pos-test (P ≤ 0.007) and retention phases (P ≤ 0.004).Conclusion: The findings suggested that the quiet eye training can improve the learning of pistol shooting skills through external guidance of visual attention.